2009
DOI: 10.1111/j.1743-6109.2008.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Erectile Dysfunction with Lesions of Cerebrovascular Accidents

Abstract: Introduction The recent human and animal studies indicate that the central supraspinal systems controlling penile erection, which are localized predominantly in the parts of the frontal lobe and limbic system, are reported to be involved in erection. Aim The purpose of this study was to elucidate the correlation of the erectile dysfunction (ED) with lesions of cerebrovascular accidents (CVA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In particular, a decrement of sexual desire was associated with a stroke lesion on the left basal ganglia; patients with lesions in the right cerebellum experienced significant ejaculatory disorders; and patients with lesion in the right pons were associated with a decrease in the International Index of Erectile Function (IIEF) score. Jeon, Yoo, Kim, Kim, and Lee (2009) demonstrated that patients with ischemic lesions of the thalamus showed a more severe degree of erectile dysfunction (ED) than those with cerebral infarctions located in any other areas. This would point out the possible role of thalamus in human penile erection supporting those preclinical studies that suggested how thalamic caudal and lateral intralaminar nuclei are involved in processing the sexual outflow from the spinothalamic pathway towards the preoptic area, amygdala, temporal lobe, and the frontal cortex.…”
Section: Etiology Of Poststroke Sdmentioning
confidence: 99%
“…In particular, a decrement of sexual desire was associated with a stroke lesion on the left basal ganglia; patients with lesions in the right cerebellum experienced significant ejaculatory disorders; and patients with lesion in the right pons were associated with a decrease in the International Index of Erectile Function (IIEF) score. Jeon, Yoo, Kim, Kim, and Lee (2009) demonstrated that patients with ischemic lesions of the thalamus showed a more severe degree of erectile dysfunction (ED) than those with cerebral infarctions located in any other areas. This would point out the possible role of thalamus in human penile erection supporting those preclinical studies that suggested how thalamic caudal and lateral intralaminar nuclei are involved in processing the sexual outflow from the spinothalamic pathway towards the preoptic area, amygdala, temporal lobe, and the frontal cortex.…”
Section: Etiology Of Poststroke Sdmentioning
confidence: 99%
“…Penile erection is a complex event controlled by vascular, hormonal, and neurological systems. [ 1 ] Depending on the context in which penile erection occurs, it is generally accepted that different central and peripheral neural and/or humoral endocrine mechanisms may participate in the regulation of this sexual response, often in a very complex fashion. [ 2 3 4 ] Erectile dysfunction (ED) is a men's health issue that is receiving overwhelming attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Post‐stroke ISA is thought to be caused by several etiologies and involves a complex interplay between psychological and organic factors . The factors reported to date include several specific characteristics of stroke (right hemisphere injury , thalamic lesions , motor impairment ), previous hypertension, diabetes and cardiac disease , various psychosocial factors (the relationship with the spouse, the fear of a new stroke ) and depression . Age is also reportedly an important factor in post‐stroke ISA .…”
Section: Introductionmentioning
confidence: 99%